Regional odontodysplasia: a review of the literature and report of a case - MAHMOUD A. HAMDAN, FALEH A. SAWAIR, LAMIS D. RAJAB, AHMAD M. HAMDAN, & IYAD KH. AL-OMARI (Paediatric Dentistry, 2004)
We present a rare case of a developmental anomaly called regional odontodysplasia or ‘ghost teeth’ in an 8·5-year-old Jordanian girl. The anomaly affected both the mandibular primary and permanent incisors, and the canines bilaterally.